Considérations sur les possibilités d’utilisation des fils techniques de feuille fibrillée de polypropylène a la confection des chaluts - Boghici, Viorica; Uzun, N. (Cercetări Marine - Recherches Marines, 2026)
The paper presents experiments carried out with the fibrillated polypropylene twines and ropes, comparing their characteristic features with those of the polyamide and polyester materials, generally used now. Their behavior in the industrial fishery pointed out that fibrillated polypropylene may he used like heavy ropes (bellylines) only, in the trawls construction.